The Development Of E-Learning Model Web-Based Mathematics Student Worksheets (LKPD) To Increase Learning Motivation Of Vocational School Students - Muh Rizky Anshori Manurung (UMSU, 2022)
This research is based on the observations of researchers, that the use of student worksheets (LKPD) as a learning resource still dominated at the SMK level. The use of LKPD which is still classical makes the class atmosphere monotonous, passive, and boring. This can be seen in the low level of student motivation. Currently, there is a learning model that utilizes information and communication technology in learning called e-learning. The problems in this study are (1) What are the stages of developing a web-based e-learning model of e-learning mathematics learning media? (2) What is the feasibility of the web-based e-learning model of the mathematical LKPD product? This research was development research (R D) with research subjects in class XI SMK YWKA Medan. This study used several instruments including lesson plans, validation sheets, and learning motivation questionnaires. The conclusion of this research is that the development of a web-based e-learning model of mathematics worksheets can increase students' learning motivation. We can find out how the process of making a web-based e-learning model of mathematics worksheets. Based on the conclusions of the results of this study, it is recommended: (1) the purpose of developing this LKPD is to introduce to students that mathematics is not a boring subject but a fun and interesting subject. (2) The development of these student worksheets must be developed again, to find out whether the development is in accordance with all the characteristics of the material and the characteristics of the students.